SEQUENTIAL STRUCTURE OF CONVERSATIONS BETWEEN SELLERS AND BUYERS AT BIBOKI ANLEU TRADITIONAL MARKET - Vincentius Mauk; Anselmus Yata Mones; Palmerya Christina Sau (Leksema: Jurnal Bahasa dan Sastra, 2025)
This research aimed at finding out the sequential structure of the interactions between sellers and buyers at the traditional market of Biboki Anleu. It employed conversation analysis (CA) to identify the interaction patterns-such as openings, adjacency pairs, insertions, extensions, and closings that reflect the social dynamics of market transaction-and ethnography of communication to understand the sociocultural context, norms, and language practices of the local community that frame their everyday communicative behaviors. The data collection was conducted through participatory observation, audiovisual recordings, and conversation transcription. The findings show that the conversation structure not only regulates the flow of communication but also conveys local cultural values such as politeness, solidarity, and communal economy. Unique expressions like owwww… are used as subtle and multimodal negotiation strategies. This study also highlights the differences of conversational structure from other traditional markets, such as those in Mexico and Manado by identifying both common patterns in buying and selling conversations and distinctive local features of the border community. Theoretically, this research expands the application of CA and ethnography of communication in local activities and enriches the understanding of interactional sociolinguistics. Culturally and linguistically, traditional markets are proven to be social spaces that shape, sustain, and transmit community identities and values through verbal and non-verbal interaction.